2022
DOI: 10.1371/journal.pone.0278597
|View full text |Cite
|
Sign up to set email alerts
|

The association of perceived leadership style and subjective well-being of employees in a tertiary hospital in Germany

Abstract: Background Professionals in the healthcare sector are a particularly vulnerable group for occupational strain due to high work-related psychological stress. For the implementation of targeted stress-prevention interventions as an important part of a workplace health management programme for all occupational groups and hierarchy levels, information about the current state of their mental health is mandatory. Hence, this study investigated the association of general well-being and different leadership styles amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…They can manifest in a positive sense, for example, through the experience of recognition, the opportunity to be creative and productive or through personal development. Psychosocial stress can also manifest in a negative sense, for example, when work stress arises from potential stressors such as qualitative and quantitative demands, negative leadership behaviour and the experience of injustice [8].…”
Section: Introduction 1work-related Stress and Strain And Their Conse...mentioning
confidence: 99%
See 1 more Smart Citation
“…They can manifest in a positive sense, for example, through the experience of recognition, the opportunity to be creative and productive or through personal development. Psychosocial stress can also manifest in a negative sense, for example, when work stress arises from potential stressors such as qualitative and quantitative demands, negative leadership behaviour and the experience of injustice [8].…”
Section: Introduction 1work-related Stress and Strain And Their Conse...mentioning
confidence: 99%
“…Health-oriented leadership styles are known to yield positive outcomes for both leaders and followers (for an overview, see [8]). Thus, future research on the wellbeing of SME leaders should focus more specifically on health-oriented leadership regarding outcomes and intervention content.…”
mentioning
confidence: 99%
“…In order to improve health and well-being at the workplace, managers have an important role, especially in terms of managing and shaping working conditions or improving job satisfaction [ 22 26 ]. For example, perceived transformational leadership style was positively associated with well-being of certain groups of health-care professionals in a hospital [ 27 ]. A systematic review on nurse leadership style and nurse satisfaction showed, that nurses reported higher job satisfaction when they worked with relational leaders than with task-oriented leaders [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Desmond [18] underlines the importance of leadership to promote well-being and states that an ethic of individualism can lead to a devaluation of leadership, making it less relevant, which consequently worsens wellbeing. Considering leadership style, some studies have shown that a style oriented toward people considerations and development promotes the well-being of the followers [19,20] and the adaptation of the team to wind changes in a firefighting situation [21]. In fact, firefighters value leaders who provide support, create mutually respectful environments, and possess the humility to admit mistakes, accepting failure within themselves and others [22], characteristics of empowering leadership.…”
Section: Introductionmentioning
confidence: 99%